Earl Scruggs and Foggy mountain breakdown : the making of an American classic - Goldsmith, Thomas, 1952- (Music in American life., 2019)
"Less than three minutes long and involving no lyrics, "Foggy Mountain Breakdown" is a banjo-led song that changed the face of American music. Composed and recorded by Earl Scruggs in 1949, the song went on to transform and modernize folk culture of the early 20th century, its effects extending far beyond bluegrass. The captivating sound of the piece helped rejuvenate the banjo, an instrument that had been vanishing from the mainstream of American music; its unforgettable twang and cadence ushered the banjo and backwoods into American popular culture by providing the soundtrack for "The Beverly Hillbillies" and "Bonnie and Clyde"; its close relationship to "Blue Grass Breakdown," a song composed by Scruggs' one-time bandleader Bill Monroe, illustrates the fungible nature of intellectual property in the early days of country music; and the song's advanced compositional techniques and technical difficulty helped distinguish Scruggs as one of a small handful of principals of acoustic music. Relying on primary sources, including interviews with Scruggs and his wife and manager, Louise, as well as with Curly Seckler, the only surviving musician from the 1949 recording, this project examines the story surrounding "Foggy Mountain Breakdown." Along the way, Goldsmith reveals much about Scruggs's career and the evolution of his influential style. No such examination about Scruggs or his famous song exists, so this project is positioned to make a strong contribution to the history of bluegrass"--